Impact of Chronic Obstructive Pulmonary Disease on Infectious Complications and Mortality in Patients With Aneurysmal Subarachnoid Hemorrhage - Lan Yang (Frontiers Media S.A., 2021)
Background and Purpose: Chronic obstructive pulmonary disease (COPD) has been associated with several complications and mortality in acutely ill patients. For patients with aneurysmal subarachnoid hemorrhage (aSAH), the association between COPD and clinical outcomes remains unclear.Methods: In this retrospective cohort study, we analyzed consecutive aSAH patients admitted to the West China Hospital between 2014 and 2019. Propensity score matching analysis and cox regression models was used to assess the association between COPD and mortality. The primary outcome was long-term mortality.Results: Using a clinical database from a large university medical center, 2,925 patients with aSAH were identified, of whom 219 (7.5%) also had COPD. Patients were followed-up for a median of 3.8 years, and during follow-up 633 patients (21.6%) died. Long-term mortality was higher in patients with COPD compared to patients without COPD in the Cox regression models [adjusted hazard ratio (HR) 1.52, 95% confidence interval (CI) 1.14–2.02]. Propensity score matching analysis also showed similar associations between COPD and mortality in hospital, at 1 year, at 2 years, and at long-term. Similarly, patients with COPD had significantly higher incidence of infections, such as pneumonia [odds ratio (OR) 3.24, 95% CI 2.30–4.56], urinary tract infection (OR 1.81, 95% CI 1.20–2.73), bloodstream infection (OR 3.83, 95% CI 1.84–7.99), and hospital infection (OR 3.24, 95% CI 2.28–4.61).Conclusions: Among aSAH patients, COPD is associated with increased mortality. COPD represents a significant risk factor for infections. Given that these are preventable complications, our findings are of clinical relevance.